Implicit and explicit attitudes toward using Facebook - Meilutė - Ribokė, Monika; Pakalniškienė, Vilmantė (Psichologija, 2018)
We already know that attitude and behavior are related and can influence each other. Greenwald and Banaji (1995) suggest that attitude can be explicit or implicit. Explicit attitude is conscious and related to such behavior. Implicit attitude is unconscious, automatic, and has more relationships with unconscious behavior. The authors of the mentioned study suggest that neither of them is “real” attitudes, but it is important to recognize both, as they can have different influences on our behavior. Facebook is the most popular social network around the world, especially across the younger generations. Researchers found that the explicit attitude toward Facebook is very positive (Johnston et al. 2013; Acılar & Mersin 2015), but there are no papers on implicit attitude. So, the purpose of this study was to find out the implicit and explicit attitudes toward using Facebook and to reveal the interrelations between these attitudes and experiences from using Facebook. The study participants consisted of 210 teenagers from a single gymnasium. Their ages were 17 (40%), 18 (50%) and 19 (10%); 41.4% of them represented boys, 58.6% – girls. Implicit attitudes were measured by the Single Attribute Implicit Association Test (SA-IAT), and the explicit attitudes – by a 21-item questionnaire regarding the attitude toward using Facebook (Kokoç & Çiçek 2011). Results showed that the majority of them have a Facebook account (N=171). Facebook users have more positive explicit attitudes, and this was related to time spent on Facebook and the number of times they connect to the social media network on a daily basis. Also, it was revealed that explicit attitude is the predictor of having an account on Facebook, and that implicit attitude had predicted the opposite. Moreover, implicit attitude does not differ between users and non-users and has no significant relationship with behavior. However, it was noticed that Facebook users were faster when pairing Facebook with pleasant rather than unpleasant words. Non-users reacted in both test conditions equally. This could mean that users unconsciously associate Facebook with pleasant feelings and may share positive implicit attitudes. However, this study has several limitations. Most of the participants were Facebook users, so the differences that were found could be inaccurate. Also, all of them were from the same gymnasium, so different results may possibly be gathered from different school populations. Therefore, the obtained results should be interpreted with caution.
Keywords: implicit attitude; explicit attitude; Facebook